Henoch - Schonlein Purpura - Wayan Retayasa; Hendra Santosa (Indonesian Pediatric Society, 1997)
Henoch-Schonlein purpura (HSP) is an immunologically mediated systemic vasculitis of small blood vessels that primarily, involves skin 100%, gastrointestinal tract 50-70%, joint 70% and the kidney 20-100%. The most common clinical manifestation are intermittent purpura, athralgia, abdominal pain and hematuria. The diagnosis of HSP based on clinical manifestation, laboratory finding and skin biopsy. The manifestation of HSP in a case of eleven year old Balinese girl were maculo papular rash of the flexor, and extensor region of the legs, butocks and fore arms, abdomininal pain and bloody stools Laboratory finding were WBC 20,000/pl, platelet count 490,000/pi, Bleeding time 3 minutes, clothing time 14 minutes PIT 23,7 second, Prothrombin time 11,2 second. The blood urea nitrogen, 16 mg/dl, creatinine, 0,66 mg/dl. Complemen C4, 39 mg/dl, IgA 355 mg/dl ASTO and CRP were negative. Histologic examinitation showed epidermis with hiperkeratosis, proliferation of subepidermic conective tissue, with magnitude of leucosites infiltration surounding small blood vesels with the conclution was according to feature of HSP.